2021
DOI: 10.20473/fmi.v55i4.24449
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cinnamomum burmannii Water Extraction Against Staphylococcus aureus, Enterobacter spp., Pseudomonas aeruginosa, and Candida albicans: In Vitro Study

Abstract: Indonesian cinnamon (Cinnamomum burmannii) is a native plant of Indonesia that has a lot of potential. The most consumed part is the bark. This study aims to examine the antimicrobial effect of Cinnamomum burmannii bark extract on various types of pathogenic microbes, namely Staphylococcus aureus, Enterobacter spp., Pseudomonas aeruginosa, and Candida albicans. An experimental study using a water extract (infusion) of Cinnamomum burmannii bark and a microbial test obtained from the Faculty of Pharmacy, Widya M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…So it is more appropriate to use the time-kill curve method to observe antibiotic activity after microorganisms are exposed to antibiotics. The information obtained is more detailed and dynamic because this method shows antibiotic activity that depends on the amount of concentration and time [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…So it is more appropriate to use the time-kill curve method to observe antibiotic activity after microorganisms are exposed to antibiotics. The information obtained is more detailed and dynamic because this method shows antibiotic activity that depends on the amount of concentration and time [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Cinnamon has an antibacterial effect on a variety of pathogenic microorganisms, including Candida albicans, Staphylococcus aureus, Enterobacter spp., and Pseudomonas aeruginosa. 26 Trans-cinnamaldehyde (trans-CNMA), a naturally occurring antibacterial and antibiofilm substance has been demonstrated to exhibit efficacy against commensal, enterohemorrhagic, and uropathogenic Escherichia coli (UPEC) strains in addition to Methicillin-resistant Staphylococcus aureus strains. Numerous CNMA analogs have recently been found to have antibiofilm actions on strains of Streptococcus pyogenes, Vibrio species, and Candida albicans.…”
Section: Introductionmentioning
confidence: 99%
“…There are at least 15 Candida species that can cause human disease, but the following five pathogens cause more than 90% of invasive infections: Candida albicans , Candida glabrata , Candida tropicalis , Candida parapsilosis , and Candida kruse i [ [1] , [2] , [3] ]. Based on the SENTRY antifungal surveillance program from 1997 to 2016, of the 20,788 isolates admitted, 46.9% were Candida albicans , 18.7% Candida glabrata , 15.9% Candida parapsilosis , 9.3% Candida tropicalis , 2.8% Candida krusei , and 6.5% Candida spp., [ 4 , 5 ]. A study in Asia found that Candida albicans caused the highest incidence of candidemia with a total of 41.36%, followed by Candida tropicalis at 25.45%, Candida glabrata at 13.93%, and Candida parapsilosis at 12.15%.…”
Section: Introductionmentioning
confidence: 99%